Sebuah PERJUANGAN PALESTINA DALAM PUISI ṬARĪQUN WĀHIDUN KARYA NIZAR QABBANI: (Analisis Semiotik) - Rivai, Muhammad Iqbal (Program Studi Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Raden Fatah Palembang, 2024)
This research aims to describe the description of Michael Riffaterre's semiotic analysis of the poem Ṭarīqun Wāhidun by Nizar Qabbani. The research method used is descriptive qualitative. The data and study are based on various sources, which are then analyzed using a semiotic approach and Riffaterre theory by readings heuristically and hermeneutically, the indirectness of expressions, models, variants, matrices and hypograms. The results of the analysis have been explained and presented in the form of words. The research subject is Ṭarīqun Wāhidun poetry, while the research object is the meaning or matrix in Ṭarīqun Wāhidun poetry. This researcher is based on an analysis of Riffaterre's semiotic reading which reveals the heuristic meaning of this poem is about a man who wants to get a rifle to go to the Palestinian battlefield. This research shows Nizar Qabbani's strong desire to fight for Palestine so that he was able to compose poetry very beautifully. The meaning is obtained based on a hermeneutical reading which is reinforced by the model